Estudo comparativo sobre efetividade de tratamentos para transtorno obsessivo compulsivo: terapia Farmacológica isolada ou em associação com Terapia Cognitivo Comportamental em Grupo? - Yoneyama, Beatriz Capparros (2019)
Obsessive-Compulsive Disorder (OCD) is a psychiatric disorder that affects about 2.5% of the general population. It is characterized by intrusive, irrational, intermittent thoughts and images that include any kind of content, these are the obsessions. Often these thoughts are followed by behaviors that evade transiently these thoughts and involve attitudes or movements, such as behaviors, these are the compulsions. It is estimated that OCD is the fourth most frequent psychiatric disorder, surpassed only by phobias, depression and chemical dependencies. Pharmacological treatment is mainly done with Selective Serotonin Reuptake Inhibitors (SSRIs). In addition, psychotherapy, especially Cognitive Behavioral Therapy (CBT) with Response Prevention Exposure (RPE) technique has been evaluated as effective. Cognitive Behavioral Therapy in Group uses RPE associated with cognitive techniques and its effectiveness in reducing the symptoms of OCD has been recently proven in our environment. Although these treatments are effective for most patients with OCD, about 20 to 40% of patients do not respond to current treatments, and other therapeutic strategies are required, such as the combined therapy strategy. It is still a matter of study how much group CBT associated with pharmacological treatment is more effective than isolated pharmacological therapy. The present study is an open experimental study with a total of 17 patients with OCD symptoms selected among psychiatric patients from the Psychiatric Outpatient Clinic of the Hospital Universitário de Santa Maria. For the research, it was created within the Ambulatory of Psychiatry, a specific outpatient clinic for OCD. As needed, the patients entered this clinic for better follow-up. Next, patients with clinical indication were offered the possibility of CBT in the group, maintaining individual pharmacological therapy. Those who agreed to participate received 12 group therapy sessions, with an initial of seven participants. At the end of therapy, five patients completed all sessions. All patients evaluated with OCD symptoms were submitted to the YBOCS scale. Improvement in obsessive and compulsive symptoms was observed in both those who completed the group CBT sessions and those who only followed pharmacological follow-up. Those patients who followed the two treatments, there was a more expressive improvementHowever, patients who gave up on psychotherapeutic follow-up had worse symptoms. It was observed that patients with OCD-associated comorbidity had worse performance on the YBOCS scale.